Impact of reaction time on 50m Freestyle performance in male swimmers: a a differential analysis across qualification levels - Zaitsev, V. S. (Theory and Practice of Physical Culture, 2025)
Objective of the study. This study investigated the relationship between start reaction time (RT) and 50-meter swimming race performance across different swimmer qualification levels. The precise nature and strength of this relationship may vary significantly depending on an athlete's skill proficiency. A large dataset comprising 2,252 competitive swimmers was analyzed and categorized into Elite (n=471), High-Level (n=574), and Medium-Level (n=1207) groups based on their competitive results.